Wind energy applications for rural areas - Bardaie, Mohd. Zohadie; Hitam, Bahanurdin (1980)
Wind energy has been used for thousands of years to propel boats and ships and to provide rotary windmills power to reduce the physical burdens of man. The present energy crisis has forced us to take a second look at wind energy as an alternative source of energy to supplement the conventional source. Wind energy has a potential for usage in rural areas. The factors related to utilizing windmills for rural applications with special reference to Malaysia are discussed. Some of the factors which are included in the discussion are wind data, windmill designs and feasibility of windmill applications in Malaysia.